ANALISIS KEPATUHAN PELAKU USAHA GARAM KONSUMSI DI KABUPATEN PATI TERHADAP REGULASI PANGAN - Kurnia Dwi Widyarini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Pati Regency is a center of salt production in Central Java, supported by its geographical potential and the demographic structure of the community, which is largely composed of salt farmers. According to data from the Ministry of Marine Affairs and Fisheries, in 2025 Pati Regency contributed 211,544.23 tons to the total production of community salt. However, the inconsistent quality of the salt produced and its inability to meet industrial salt specifications necessitate a backward examination of the underlying factors causing the inconsistency in salt quality in Pati Regency despite its considerable potential. Therefore, an analysis was conducted on the compliance of consumption salt industry in Pati Regency with applicable regulations through the examination of secondary data, including product legality and fulfillment of registration requirements for obtaining distribution permits during the 2019–2025 period, as well as the results of post-market inspections of production facilities in 2025. Based on the findings of this study, it was determined that the compliance of consumption salt industry in Pati Regency with regulations remains relatively low, particularly in the implementation of Good Manufacturing Practices (GMP/CPPOB). Data from the Processed Food Registration System (e-reg.pom.go.id/ereg and ereg-rba.pom.go.id) for the 2019–2025 period indicate that 39.74% of consumption salt industry did not continue the product legalization process, while only 15.38% had undertaken CPPOB certification procedures. These findings are consistent with the post-market inspection results, which showed that 83.33% of consumption salt production facilities did not implement CPPOB in accordance with regulatory requirements. ABSTRAK Kabupaten Pati merupakan sentra produksi garam di Jawa Tengah yang didukung potensi geografis dan struktur demografis masyarakat sebagai petani tambak. Berdasarkan data Kementerian Kelautan dan Perikanan, Kabupaten Pati pada tahun 2025 mampu berkontribusi sebesar 211.544,23 ton dari jumlah produksi garam rakyat. Namun kualitas garam yang dihasilkan yang tidak konsisten dan belum mampu memenuhi spesifikasi garam industri, maka perlu ditarik ke belakang permasalahan yang menjadi penyebab inkonsistensi kualitas garam di Kabupaten Pati di tengah potensi yang begitu besar. Oleh karena itu dilakukan analisa kepatuhan pelaku usaha garam konsumsi di Kabupaten Pati terhadap regulasi melalui penelusuran data sekunder berupa legalitas produk dan pemenuhan persyaratan dalam registrasi produk untuk mendapatkan izin edar pada kurun waktu tahun 2019-2025, serta hasil pemeriksaan sarana produksi post-market pada tahun 2025. Berdasarkan hasil penelitian ini diketahui bahwa kepatuhan pelaku usaha garam konsumsi di Kabupaten Pati terhadap regulasi cukup rendah terutama pada penerapan Cara Produksi Pangan Olahan yang Baik (CPPOB). Sistem Registrasi Pangan Olahan (e-reg.pom.go.id/ereg dan ereg-rba.pom.go.id) periode tahun 2019-2025 menunjukkan 39,74% pelaku usaha garam konsumsi tidak melanjutkan proses legalisasi produk dan hanya 15,38% yang sudah melakukan proses sertifikasi CPPOB. Hasil tersebut sejalan dengan hasil pemeriksaan post-market yang menunjukkan bahwa 83,33% sarana produksi garam konsumsi tidak menerapkan CPPOB sesuai ketentuan.